Curadoria de conteúdo: proposta de um método para plataformas digitais. - Leão, Gabriela Viana (2020)
The purpose of this Final Report is to describe the proposal of a Digital Content Curation method, elaborated as a product of the Master in Creative Industries of the Catholic University of Pernambuco. The methodology aims to contribute to the quality of materials posted on the internet and social networks, by optimizing the information published online and in the digital environment. The goal is to try to make the research process easier for producers and web users, since most of the content is scattered and unclear about sources. The proposal is to compile information gathered from official and institutional organizations for the elaboration of a digital material that delivers a broad view analysis of a given event / news, following criteria in the method presented here. As a demonstration of this method, a pilot video for Instagram and YouTube was elaborated that reports the last chemical attack in Syria in April 2018. This work becomes a small step that can be applied and who knows, enhanced in the field of communication.